An empirical investıgatıon about the relationship between financial risk tolerance and overconfidence in Turkey - Çelik, Mustafa Okan (My University, 2016)
TÜRKİYE’DE FİNANSAL RİSK TOLERANSI VE AŞIRI GÜVEN ARASINDAKİ İLİŞKİ ÜZERİNE BİR UYGULAMA Finansal risk toleransı insan hayatında önemli bir rol oynamaktadır. Bireylerin yatırım kararları asıl olarak riske karşı tutumlarına dayanmaktadır. Aşırı güven de bireylerin önemli bir özelliğidir. Gelişmekte olan davranışçı finans alanı finansın klasik bir alanı olan riske daha farklı bir açıdan bakılmasını sağlar. Davranışsal önyargılar insanların gerçekte nasıl davrandıklarının görülmesinde yardımcı olur. Aşırı güven eskiden beri ispatlanmış bir davranışsal önyargıdır ve literatürde önemli şekilde desteklenmiştir. Araştırmada finansal risk toleransı ve aşırı güven arasındaki ilişki ölçüldü. Aynı zamanda belli demografik bilgiler kullanıldı. Araştırma metodu bağımsız gruplar t-testi ve korelasyon analizleriydi. Örnek Marmara, Boğaziçi, Yeditepe ve Çukurova üniversitelerinin İktisadi ve İdari Bilimler Fakültelerinde okuyan 187 öğrenciden oluşmaktadır. Genel hatlarıyla finansal risk toleransı ve aşırı güven arasında anlamlı bir ilişki bulanamadı. Sadece kadınların dörttebirlik incelemesinde aşırı güven ve finansla risk toleransı arasında anlamlı bir ilişkiye rastlandı. Bir diğer bulgu ise kadınların finansal risk toleransının erkeklerden daha düşük olmasıydı. Davranışsal Finans, Finansal Risk Toleransı, Aşırı Güven

AN EMPIRICAL INVESTIGATION ABOUT THE RELATIONSHIP BETWEEN FINANCIAL RISK TOLERANCE AND OVERCONFIDENCE IN TURKEY Financial risk tolerance plays an important role in our lives. Individuals' investment decisions are mainly based on attitude towards risk. Overconfidence is also an important characteristic of individuals. The emerging field of behavioral finance enables us to look at different sides of a classical topic of finance such as risk. The behavioral biases help us see how people actually behave. Overconfidence is a well-established bias and gained great support in the literature. It has implications in the area of finance. In our research we measured the relationship between financial risk tolerance and overconfidence. We also utilized certain demographic information. Our methods of analysis were independent sample t-tests and correlation analyses. The sample consisted of 187 students from Marmara, Boğaziçi, Yeditepe, and Çukurova universities. The students are from Faculty of Economics and Administrative Sciences. We could not find a significant relationship between financial risk tolerance and overconfidence in general. The only significant relationship was between females' quartile-based overconfidence and financial risk tolerance. Another finding was that females have lower financial risk tolerance than males. Behavioral Finance, Financial Risk Tolerance, Overconfidence
Keywords: Muhasebe; Yönetim